Brain activation during phonological and semantic processing of Chinese characters in deaf signers - Li, Yanyan; Peng, Danling; Liu, Li; Booth, James R.; Ding, Guosheng (Frontiers in Human Neuroscience, 2014)
Previous studies found altered brain function in deaf individuals reading alphabetic orthographies. However, it is not known whether similar alterations of brain function are characteristic of non-alphabetic writing systems and whether alterations are specific to certain kinds of lexical tasks. Here we examined differences in brain activation between Chinese congenitally deaf individuals (CD) and hearing controls (HC) during character reading tasks requiring phonological and semantic judgments. For both tasks, we found that CD showed less activation than HC in left inferior frontal gyrus, but greater activation in several right hemisphere regions including inferior frontal gyrus, angular gyrus and inferior temporal gyrus. Although many group differences were similar across tasks, greater activation in right middle frontal gyrus was more pronounced for the rhyming compared to the meaning task. Finally, within the deaf individuals better performance on the rhyming task was associated with less activation in right inferior parietal lobule and angular gyrus. Our results in Chinese CD are broadly consistent with previous studies in alphabetic languages suggesting greater engagement of inferior frontal gyrus and inferior parietal cortex for reading that is largely independent of task, with the exception of right middle frontal gyrus for phonological processing. The brain behavior correlations potentially indicate that CD that more efficiently use the right hemisphere are better readers.